2006
DOI: 10.1017/s0033291706007434
|View full text |Cite
|
Sign up to set email alerts
|

Integrated specialist assessment of older people and predictors of care-home admission

Abstract: In this at-risk group, integrated assessment offers a means of potentially both delaying care-home admissions and taking account of a wider range of factors in placement decisions. Such an approach is viewed as an important policy goal both in the UK and internationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…12,17,22,51,53,56,57,91 In the studies that showed a decrease in institutionalization, 48,64,67 the mean effect size was small (0.21). 48,67 In 2 of 5 studies, hospital admission decreased (mean effect size = 0.66).…”
Section: Description Of the Case Management Interventionsmentioning
confidence: 95%
“…12,17,22,51,53,56,57,91 In the studies that showed a decrease in institutionalization, 48,64,67 the mean effect size was small (0.21). 48,67 In 2 of 5 studies, hospital admission decreased (mean effect size = 0.66).…”
Section: Description Of the Case Management Interventionsmentioning
confidence: 95%
“…A full description of the criteria has been published (Challis et al, 2004). The data, on the existence and identification of a range of needs, from before the SAP were available from a randomized trial of assessment practice for older people, the findings of which have already been reported (Challis et al, 2004; Clarkson, Venables, Hughes, Burns, & Challis, 2006; Venables, Clarkson, Hughes, Burns, & Challis, 2006).…”
Section: Participants and Methodsmentioning
confidence: 99%
“…That said, the data from the social services domiciliary sample would seem to suggest that at any one time there are a number of people in the community with considerable ongoing care needs who receive relatively little formal support. In the light of evidence that specialist integrated assessment may potentially defer the care home admission of older people at risk, 174 the fact that more than half of care home entrants had not been seen by specialist mental health services was also noteworthy.…”
Section: Implications For Local Service Providersmentioning
confidence: 99%